2023
DOI: 10.1111/aogs.14536
|View full text |Cite
|
Sign up to set email alerts
|

Does induction of labor at 41 weeks (early, mid or late) improve birth outcomes in low‐risk pregnancy? A nationwide propensity score‐matched study

Abstract: Introduction: This study aimed to assess whether induction of labor at 41 weeks of gestation improved perinatal outcomes in a low-risk pregnancy compared with expectant management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…In addition, induction of labor increased the rate of APGAR 5 min <7 in the first group. This is concordant with other published data (10,28) but also in contrast to other studies (14,15,19,21). In contrast, the rate of meconiumstained amniotic fluid or pH-value of the umbilical cord artery remained unaffected due to labor induction.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In addition, induction of labor increased the rate of APGAR 5 min <7 in the first group. This is concordant with other published data (10,28) but also in contrast to other studies (14,15,19,21). In contrast, the rate of meconiumstained amniotic fluid or pH-value of the umbilical cord artery remained unaffected due to labor induction.…”
Section: Discussionsupporting
confidence: 92%
“…Analysis of delivery mode depending on obstetric management indicated that induction of labor enhanced the rate of secondary c-section and significantly decreased the rate of spontaneous deliveries while the rate of assistant vaginal deliveries remained unaffected. This is in line with some other studies, showing increased c-section rate subsequent to induction of labor beyond term (10,21,22,28,30,31). However, published data remain controversial, since other published studies report unchanged rate of c-section due to labor induction (14,15,20,26,27,(32)(33)(34).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations